Extensive Imitation is Irrational and Harmful* - Eyster, Erik; Rabin, Matthew (Quarterly Journal of Economics, 2014)
Abstract Rationality leads people to imitate those with similar tastes but different information. But people who imitate common sources develop correlated beliefs, and rationality demands that later social learners take this correlation into account. This implies severe limits to rational imitation. We show that (i) in most natural observation structures besides the canonical single-file case, full rationality dictates that people must “anti-imitate” some of those they observe; and (ii) in every observation structure full rationality dictates that people imitate, on net, at most one person and are imitated by, on net, at most one person, over any set of interconnected players. We also show that in a very broad class of settings, any learning rule in which people regularly do imitate more than one person without anti-imitating others will lead to a positive probability of people converging to confident and wrong long-run beliefs.